1988
DOI: 10.1161/01.atv.8.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Prostacyclin, thromboxane A2, and prostaglandin E2 formation in atherosclerotic human carotid artery.

Abstract: Prostaglandin (PG) formation In 16 atherosclerotic human carotid endarterectomy specimens was compared systematically with that of normal carotid artery from seven white pigs and six rhesus monkeys. Prostacyclin (PGI2) formation (plcomoles 6-keto-PGF 1t /2 mln/100 ^9 homogenate protein plus 2 mM glutathlone [GSH]) of nonatheromatous Intlma adjacent proximal (276 ± 32, mean ± SEM) or distal (271 ± 14) to carotid plaque was comparable to that of normal carotid artery from white pig (272 ± 25, NS) and rhesus monk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…22 Taken together, all these elements suggest that Ox-LDL itself could trigger the decrease in prostacyclin synthesis observed in atherosclerotic lesions. 12 As well as inhibiting basal formation of prostacyclin, Ox-LDL chronically incubated with endothelial cells almost abolished the receptor-dependent stimulated release of prostacyclin, suggesting that the alteration is not specific for one class of receptor. Moreover, AAinduced 6-keto-PGF, a formation did not appear to be dose-dependently related.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…22 Taken together, all these elements suggest that Ox-LDL itself could trigger the decrease in prostacyclin synthesis observed in atherosclerotic lesions. 12 As well as inhibiting basal formation of prostacyclin, Ox-LDL chronically incubated with endothelial cells almost abolished the receptor-dependent stimulated release of prostacyclin, suggesting that the alteration is not specific for one class of receptor. Moreover, AAinduced 6-keto-PGF, a formation did not appear to be dose-dependently related.…”
Section: Discussionmentioning
confidence: 90%
“…During the atherosclerotic process, however, Ox-LDL is probably chronically in contact with the endothelial layer. Previous work showed that prostacyclin release is selectively decreased at the level of the atherosclerotic lesion compared with the surrounding area 12 as well as in smooth muscle cells isolated from atherosclerotic rabbit aorta, in which cyclooxygenase and prostacyclin synthase activities appear to be reduced. 10 The mechanism for the decrease in prostacyclin is unknown, but three lines of evidence support an oxidation-dependent alteration.…”
Section: Discussionmentioning
confidence: 98%
“…However, a rapid increase in shear-induced platelet activation may aggravate the imbalance between thromboxane and prostacyclin at sites of severe atherosclerosis, because it has been shown that prostacyclin synthesis is deficient in atherosclerotic carotid plaques. 32 Such an imbalance could rapidly develop during heavy alcoholic intoxication and lead to local thrombus formation if not simultaneously compensated for by enhanced prostacyclin formation. Because fairly heavy physical activity is needed to stimulate prostacyclin formation, 27 bed rest and severe alcoholic intoxication could be a harmful combination for individuals with atherosclerotic arteries.…”
Section: Discussionmentioning
confidence: 99%
“…36 The constrictor responses to ET-1 in mesenteric arteries are potentiated by indomethacin, suggesting a release of prostacyclin. 51 Atherosclerosis may increase 52 or decrease 53 the production of prostacyclin. Our finding, that indomethacin did not augment the constrictor effects of ET-1 on large arteries in normal and atherosclerotic monkeys, suggests that vasodilator prostaglandins are not released in response to ET-1 in the cynomolgus monkey.…”
Section: Responses After Indomethacinmentioning
confidence: 99%